Tożsamość hybrydyczna - Szczęsna, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2004)
The article points to contemporary revaluations and reinterpretations taking place in the sphere of signification and construction of the cultural text whose vital feature becomes the emergence of semiotic, stylistic and media-related hybrids (advertising, the Internet). Hybrid identities inspire new forms of textuality characterised by the semiotic (semantic and syntactic) co-dependence of sign systems co-generating the message. Hybridization leads to vital changes in the functioning of the sign and of the text while a textual agreement becomes the main rule governing the new forms of textuality. The hybrid nature of commercial advertising is underlined by the latter’s ontic character: it is simultaneously a singular text, a genre, a form of discourse, an element of social interexchange and a component of the marketing process. Its multi-media, transsemiotic and intertextual nature combines textual forms until now considered stylistically incompatible or even self-excluding.